The Role of Perspective and Spatial Relationships in Still Life Painting - Tolibova Umida Davlat qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
ANNOTATION: This article examines the role of perspective and spatial relationships in enhancing the realism and expressiveness of still life paintings. It highlights pedagogical methods for teaching students to observe depth, proportion, and object placement to create visually coherent and engaging compositions. The study draws upon Shovdirov S.A.’s research to emphasize effective approaches in visual arts education.